(untitled) (Research, Society and Development, 2022)
Introduction: The mental health and life quality of medical students can directly and indirectly affect in their academic performance, skills and even their approach towards patients. Studies increasingly reveal the importance of the educational environment as one of the determinants factors of mental and physical health. This systematic review aimed to assess numerous aspects of medical students’ life quality and its consequences. Methods: This study included the following databases: Nacional Library of Medicine (PUBMED), Scientific Electronic Library Online (SciELO), Latin American and Caribbean Heatlh Sciences Literature (LILACS) and Google Scholar, using the descriptors “STUDENTS, MEDICAL x QUALITY OF LIFE x ANXIETY x DEPRESSION” Results: Of the 5.492 studies found, 45 were read in full text, and 14 were qualified for the systematic review. Conclusion: When quality of life of medical students is assessed, it becomes evident that psychological wear is present during the medical graduation degree. New studies are needed to identify the determining factors for these changes in the quality of life and how they influence the academic education of new professionals.